2023
DOI: 10.1007/s40719-023-00251-x
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Factors and Pediatric Injury

Abstract: Purpose of Review The goal of this review is to describe how socioeconomic status (SES) is evaluated in the pediatric trauma literature and further consider how differences in SES can lead to inequities in pediatric injury. Recent Findings Insurance status, area-level income, and indices of socioeconomic deprivation are the most common assessments of socioeconomic status. Children from socioeconomically disadvantaged backgrounds experience higher rates of firearm-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…19 A 2023 study on SES related to pediatric injury found that the most deprived quintile had half the number of SRIs compared with more advantaged groups. 20 Using insurance status as a surrogate for SES, our study differs in that a majority of SRIs occurred in patients with government or public health insurance, whereas private insurance was less common.…”
Section: Discussionmentioning
confidence: 99%
“…19 A 2023 study on SES related to pediatric injury found that the most deprived quintile had half the number of SRIs compared with more advantaged groups. 20 Using insurance status as a surrogate for SES, our study differs in that a majority of SRIs occurred in patients with government or public health insurance, whereas private insurance was less common.…”
Section: Discussionmentioning
confidence: 99%
“…The need to exclude the parental employment variable contrasts with findings in the literature indicating that SES has an impact on a child’s ability to recover from injury and post-injury therapy [ 62 ]. Lower family income has been associated with a higher percentage of pediatric TBI mortality [ 63 ] and higher levels of emotional difficulties and conduct problems at 12 months post-injury [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…3,8,18 Many studies have described the disproportionate burden of injury experienced by children who live in socioeconomically disadvantaged environments. [18][19][20][21] Three equity gaps have been broadly described: differences in injury epidemiology (including frequency and severity), 3,17,22 differences in postinjury care (including access to resources such as rehabilitation), 18,19 and differences in child and family resilience to recover and thrive after sustaining such an injury. 7,23,24 This study demonstrated that patients living in neighborhoods with a higher MCDI were at a significantly higher risk of sustaining a severe TBI than patients living in more socioeconomically advantaged neighborhoods.…”
Section: Discussionmentioning
confidence: 99%
“…There have been other studies that have demonstrated that injuries related to interpersonal violence are higher in communities that are more deprived, due to a higher risk of abuse, assault, and firearms. 14,20 Kelly et al demonstrated that Black, Hispanic, and Native American children had worse clinical outcomes. 3 Black children may experience more severe injuries as a result of interpersonal violence from assault or firearms at a higher rate than other racial groups.…”
Section: Discussionmentioning
confidence: 99%